(untitled) (International Journal of Physiology, 2019)
Background Sitting is the main everyday ‘activity’ of contemporary people. In In 1997, the number of hours spent weekly on computer was 5.9, whereas in 2003 it reached 14.6 per week. The latest research confirms the significant impact of the sitting posture on the respiratory system. The aim of this study to compare the respiratory chest movements based on the type of chair used. Aims & Objectives 1.Comparison of respiratory amplitudes in females in chair 1 and chair 2 2.Comparison of respiratory amplitudes in males in chair 1 and chair 2 3.Comparison of respiratory amplitudes(in males & females) in relation with weight. Materials & Method The present study was conducted in the Research laboratory, Dept. of Physiology, RVMIMS, Laxmakkapally, Siddipet. A total of 60 subjects were selected (30 males & 30 females) between age group 17–25 years. Respiratory movements and weight were recorded. Respiratory movements were recorded using stethograph (respiratory belt) and Weight using weighing machine. The study covered respiratory chest movement assessment of the subjects in two different chairs. Results All measured values were statistically analyzed using Window Stat software. Paired t-test analysis and ANOVA has been used to find out the significant p. Amplitudes for the first chair (298.4mV) reached a higher average level than for the second one (268.9mV).The study did not show correlation between body weight and respiratory amplitudes in first chair and second chair. The comparison clearly shows a higher respiratory amplitude for females(300.3±36.9) in first chair as compared to men(296.5±43). Conclusion The study results conclude that there is a considerable change in the chest respiratory movements depending on the orientations of joints and muscle activation. Respiratory movements in chair 1 (upright position) are higher than chair 2 (slumped position). Thus an emphasis should be made on changing the seats’ physical activity and its effect on respiratory system.